2009
DOI: 10.4314/ijbcs.v2i4.39778
|View full text |Cite
|
Sign up to set email alerts
|

Studies on raising and preparation of planting stock of three indigenous forest timber species in Nigeria

Abstract: Seed germination studies, seedling growth, planting stock preparation and field trial at planting espacement of 3 m x 3 m were evaluated in the study. Soaking seeds in tap water for ten days with daily replacement of water yielded 100% seed germination for A. africana, 100% for A. boonei and 90% for A. lebbeck respectively in light condition. These values were better than those obtained in the control and dark condition. Growth values observed in forest topsoil were significantly different from those from rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The growth response of seedlings in the topsoil with regards to growth parameters viz; height, leaf number and leaf area was significantly higher (p<0.05) when compared with the rest of the treatments. This observation conforms with the assertions of Ehiagbonare, and Onyibe [24] who reported better seedlings growth of Albizia lebbeck and other tree like Alstonia boonei and Afzelia Africana on topsoil. Also, the observed maximum value recorded in leaf number, height, stem diameter and leaf area for seedlings grown on topsoil media shows that topsoil had the best effect on the seedlings growth parameters and this could be attributed to its high-water retention and high organic matter content compared to other media.…”
Section: Discussionsupporting
confidence: 92%
“…The growth response of seedlings in the topsoil with regards to growth parameters viz; height, leaf number and leaf area was significantly higher (p<0.05) when compared with the rest of the treatments. This observation conforms with the assertions of Ehiagbonare, and Onyibe [24] who reported better seedlings growth of Albizia lebbeck and other tree like Alstonia boonei and Afzelia Africana on topsoil. Also, the observed maximum value recorded in leaf number, height, stem diameter and leaf area for seedlings grown on topsoil media shows that topsoil had the best effect on the seedlings growth parameters and this could be attributed to its high-water retention and high organic matter content compared to other media.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, effects of growth media on germination and emergence of seedlings were significant with growth media having top soil in their composition forming better media for germination; which is in line with the findings of Adeoluwa et al (2014) in the growth study of Ficus retusa. In addition, Ehiagbonare and Onyibe (2008) observed that forest topsoil supported better seedlings growth of Albizia lebbeck, Alstonia boonei and Afzelia africana than river sand. Germination percentages were highest for Saki and the most appropriate medium being the topsoil + sawdust combination.…”
Section: Discussionmentioning
confidence: 92%
“…Often, a OH group at C(3) is observed in triterpenoids, but in compound 1, the OH group is positioned in the side chain, which was confirmed by long-range correlations of HÀC(31) (d(H) 3.41) to C(22) (d(C) 30.1) and C(33) (d(C) 8.5) in the HMBC spectrum. In addition, the correlation CH 2 (1)/CH 2 (6) to C(4) (d(C) 42.8) and CH 2 (1)/HÀC(5) to C(3) (d(C) 30.8) clearly evidenced the structure of ring A without OH substitution at C(3). From the HMBC of HÀC (21) to C(29) (d(C) 17.9) and C(30) (d(C) 34.2), the position of the side chain at C(21) was determined ( Fig.).…”
mentioning
confidence: 95%
“…All the spectral data for 6 were found to be similar to those of 2-hydroxy-1,3,4-trimethoxyanthraquinone [21], except for the additional AcO group. A singlet (d(H) 7.68) and two doublets (d(H) 7.22 and 7.94) in the 1 H-NMR spectrum in the aromatic region clearly indicated the position of the AcO group at ring A, either at C (6) or C (7). The NOESY correlation between (d(H) 3.70) MeOÀC(3) and MeOÀC(4) (d(H) 3.30) clearly showed that the two MeO groups must be placed at adjacent C-atoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation